CARDIAC MAGNETIC RESONANCE IMAGING IN EARLY DIAGNOSTICS OF MYOCARDIAL INFLAMMATION AFTER COVID-19: CASE SERIES AND LITERATURE REVIEW - Zdravković, Marija; Klašnja, Slobodan; Popović, Maja; Đuran, Predrag; Manojlović, Andrea; Brajković, Milica; Marković, Olivera; Jovanović, Igor; Branković, Marija; Viseslav (Srpski medicinski časopis Lekarske komore, 2021)
Although, in the beginning, it was considered a respiratory infection with bilateral pneumonia as its main manifestation, COVID-19 is more of a multisystemic disease with various extrapulmonary manifestations. Cardiovascular manifestations are caused by direct viral involvement or by the effects of different cytokines on the myocardium and can occur during the acute phase of the disease or in the post-acute stadium. The most common cardiovascular symptoms in the post-acute COVID-19 stadium are fatigue, shortness of breath, chest pain, and palpitations. Routine cardiovascular diagnostics in these patients is usually without significant findings, although underlying myocardial inflammation may be present. Myocardial damage can also be the substrate for the worsening of heart failure and different potentially life-threatening arrhythmias, which is extremely important for further treatment and prognosis. Cardiac magnetic resonance imaging is a sophisticated, non-radiating imaging modality that can provide important information regarding left and right ventricle volumes and function, tissue characterization, and scar quantification. It is the golden standard in non-invasive diagnostics of myocarditis. In patients with prior COVID-19 infection and cardiovascular symptoms, typical signs of myocarditis, including myocardial edema, necrosis, and myocardial scarring, may be seen in cardiac magnetic resonance. Also, there are sophisticated cardiac magnetic resonance imaging modalities that can register subtle changes in the myocardium, in terms of myocardial inflammation, without visible signs in standard sequences. We present a case series of patients with different myocardial inflammation patterns, followed by a comprehensive review of potential pathophysiological mechanisms, complications, treatment and prognosis of patients with myocarditis or pericarditis after COVID-19.